Digital finance and corporate green investment: a perspective from institutional investors and environmental regulations - Javeed, Sohail Ahmad; Latief, Rashid; Cai, Xiang; Ong, Tze San (Elsevier, 2024)
Corporate green investment is a new possibility that may overcome environmental challenges and other economic concerns. The excessive use of industrial gases and chemicals concerns all authorities. Conversely, the traditional economy has rapidly transformed into a digital economy, particularly in China. The digital financing system in China edifies a new face of the industry and economy that stimulates company social action. This study unfolds the three critical aspects of digital finance that pertain to corporate green investments in highly polluting companies. After a series of econometric tests, the research demonstrated how companies can be persuaded to make green investments using digital financing. It emphasised how institutional investors support corporate green investments and act as moderators to strengthen the relationship between digital finance and corporate green investment. Furthermore, it unveiled the critical function of environmental regulations for green investment improvement and the reason for positivity among digital financing and company green investment. With the heterogeneity test, the study segregated state-owned and non-state-owned firms. It discovered that state-owned businesses use the digital finance function more than non-state-owned businesses. This weak connection can be vital for non-state-owned firms through institutional investors and environmental regulations as moderators. Therefore, a fresh viewpoint in the digital age can encourage policymakers to improve corporate social action and promote a green economy.